(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
Today’s media appearance is shifted more than ever towards the web dimension of the social interactions. This creates new factors of the environment and establishes the need for an adequate reaction from both the traditional printed and electronic issues, and the online forms of journalistic expression. We are witnessing the escalation of the so called “fake news”. It is not so much a consequence of the public’s imagination, but the intensified online interaction, the digitalisation and the global development of Internet. The presence of the subject in the media agenda and the secondary analysis of some publicly available statistical data outline a number of problems.